solving by substitution method

hodasmom

New member
Joined
Sep 22, 2008
Messages
3
The problem is x-3y=6, 3x+5y=-10.
I solved 3x+5y=-10
3x-3x+5y=-10-3x
5y=-10-3x
_ _
5 5
y=-2-3x
AND THEN
x-3(-2-3x)=6
x+6+9x=6
10x+6=6
10x+6-6=6-6
10x=0
Somehow I dont think this is right. HELP!!!!
 
hodasmom said:
The problem is x-3y=6, 3x+5y=-10.
I solved 3x+5y=-10
3x-3x+5y=-10-3x
Code:
                      5y  =-10 - 3x
                       _     _   _ 
                       5     5   5
y=-2-(3/5)x <<<<< Now continue
AND THEN
x-3(-2-3x)=6
x+6+9x=6
10x+6=6
10x+6-6=6-6
10x=0
Somehow I dont think this is right. HELP!!!!
 
much easier to solve for x in the first equation ...

x = 3y+6

now substitute (3y+6) for x in the second equation ... solve for y, then go back to your sub equation and find x.

btw, your solution for x is correct ... you just took the long road to Hong Kong.
 
skeeter said:
much easier to solve for x in the first equation ...

x = 3y+6

now substitute (3y+6) for x in the second equation ... solve for y, then go back to your sub equation and find x.

btw, your solution for x is correct ... you just took the long road to Hong Kong.

O.K. Is the answer x=1,y=2
 
sorry, no. I told you that your value for x was correct, didn't I ?

x = 3y+6

sub ...

3(3y+6) + 5y = -10

try again.
 
hodasmom said:
10x=0
Somehow I dont think this is right. HELP!!!!
mom, seems you're unaware that if 10x = 0, then x = 0; 10 times 0 = 0 ;
give x any other value than 0 and 10x will not equal 0.
Hope that helps.
 
hodasmom said:
The problem is

x - 3y = 6, >>>>> x = 6 + 3y .........................(1)

3x+5y=-10. .......................................(2)

3(6 + 3y) + 5y = -10

18 + 9y + 5y = -10

14y = - 28

y = -2 ........................................(3)

Using (3) in (2)

x = 6 + 3*(-2)

x = 0........................................(4)


check

x - 3y = 0 - 3*(-2) = 6 ................checks

3x + 5y = 3*0 + 5*(-2) = -10.........checks






I solved 3x+5y=-10
3x-3x+5y=-10-3x
5y=-10-3x
_ _
5 5
y=-2-3x
AND THEN
x-3(-2-3x)=6
x+6+9x=6
10x+6=6
10x+6-6=6-6
10x=0
Somehow I dont think this is right. HELP!!!!
 
Top